2017
DOI: 10.1016/j.mser.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Injectable scaffolds: Preparation and application in dental and craniofacial regeneration

Abstract: Injectable scaffolds are appealing for tissue regeneration because they offer many advantages over pre-formed scaffolds. This article provides a comprehensive review of the injectable scaffolds currently being investigated for dental and craniofacial tissue regeneration. First, we provide an overview of injectable scaffolding materials, including natural, synthetic, and composite biomaterials. Next, we discuss a variety of characteristic parameters and gelation mechanisms of the injectable scaffolds. The advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
170
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 216 publications
0
170
0
3
Order By: Relevance
“…The intelligent character of the copolymers obtained is based on the phase transition LCST that presented around a temperature range T~30-35°C, values close to the body temperature (37.4°C), giving the material potentiality for its use in biomedical applications. In the literature it has been reported that by adding a new component to PNIPAm (covalently bound or by physical mixtures) it is possible to change its LCST transition temperature to higher or lower values 11,12,19 . What has been mentioned is that when some hydrophilic phase is added to the PNIPAm, the LCST is displaced at higher temperatures 5 , while in the presence of compounds with greater hydrophobic character, the opposite effect occurs 2,20 .…”
Section: Study Of the Lcst Of The Synthesized Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The intelligent character of the copolymers obtained is based on the phase transition LCST that presented around a temperature range T~30-35°C, values close to the body temperature (37.4°C), giving the material potentiality for its use in biomedical applications. In the literature it has been reported that by adding a new component to PNIPAm (covalently bound or by physical mixtures) it is possible to change its LCST transition temperature to higher or lower values 11,12,19 . What has been mentioned is that when some hydrophilic phase is added to the PNIPAm, the LCST is displaced at higher temperatures 5 , while in the presence of compounds with greater hydrophobic character, the opposite effect occurs 2,20 .…”
Section: Study Of the Lcst Of The Synthesized Copolymersmentioning
confidence: 99%
“…In the case of hydrogels sensitive to changes in temperature are characterized by having a lower critical solution temperature (LCST) 9,10 . Among the smart polymers we can mention PNIPAm, which is a non-biodegradable polymer having an LCST of approximately 32-34°C (close to human body temperature 37.4°C) 7,11 . However, being a synthetic polymer, the PNIPAm could present problems of biocompatibility and biodegradability, so it is of great interest, the incorporation of a phase that can improve this condition, especially if it is intended to be used in some biomedical applications 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The injectable hydrogels are paid more attention as they can be injected to the damaged part in situ with easily taking on complex shape and adhering to the surrounding tissues during hydrogels formation . Moreover, the injectable system have some advantages over prefabricated scaffold, including easy application, avoiding operational trauma and improving patient compliance and comfort, which have been paid more attention in tissue engineering scaffolds …”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, the injectable system have some advantages over prefabricated scaffold, including easy application, avoiding operational trauma and improving patient compliance and comfort, which have been paid more attention in tissue engineering scaffolds. 20,21 Alginate (Alg), a natural copolymer of polysaccharides, is derived from algae. Alg is widely used in food and pharmaceutical industries with favorable degradability and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-and material-based strategies to bone regeneration have been successfully applied in the clinic [7], yet most approaches involve pre-formed scaffolds that require invasive surgery for implantation. Minimally-invasive delivery of cells and materials is preferable to minimize surgical complications and the possibility of injection [8]. In particular, delivery of moldable materials via injection has the advantage that they can conformally fill even irregularly-shaped defects.…”
mentioning
confidence: 99%